METHODOLOGICAL FOUNDATIONS OF USING THE POSSIBILITIES OF ARTIFICIAL INTELLIGENCE IN THE DEVELOPMENT OF MOTIVATION TO LEARN ENGLISH AMONG STUDENTS - Jurabekova Madinabonu (Western European Studies, 2024)
This paper will discuss the methodological foundations of integrating artificial intelligence (AI) into students' English language learning. As a result of technological advances, teachers are increasingly using AI technology to improve language acquisition. This article aims to provide suggestions for effective approaches to the use of AI in English language teaching by analysing the state of AI in modern education and the possibilities of using it for language acquisition. The article emphasises a number of important factors including adaptive learning, flexible feedback and interactive learning based on various cited materials such as academic journals, research articles and teaching materials. By understanding the methodological principles behind the use of artificial intelligence in English language teaching, teachers will be able to use technology effectively to maximise student learning outcomes.
Keywords: artificial intelligence; personalised learning; adaptive feedback